Target of Improving Poverty Alleviation Trek: A Case of Bangladesh (Asian Journal of Social Science Studies, 2017)
The study aims to provide a systematic outline of Bangladesh development progress since its independence in 1971 to the present epoch regarding poverty alleviation trek. Though Bangladesh has achieved considerable progress in reducing head count poverty and poverty gap ratio but hunger poverty reduction and employment generation should be given more attention at the present time. According to MDG report last 2014; Bangladesh has made commendable progress in respect of eradication of poverty and hunger. It has sustained a GDP growth rate of 6 percent or above in recent years that has played a positive role in eradicating poverty. The main objective of the study is to investigate some important issues like poverty, inequality, unemployment scenery and social instability in the context of Bangladesh. The method of the study has been used to identify and review of Bangladesh government and UN published report analytically. The robust growth has been accompanied by corresponding improvements in several social indicators such as increased life expectancy and lower fertility rate despite having one of the world’s highest population densities. This inclusive growth has resulted in impressive poverty reduction from 56.7 percent in 1991-92 to 31.5 percent in 2010; the rate of reduction being faster in the present decade than the earlier ones (MDG report last, 2014). The latest HIES 2010 data shows that the incidence of poverty has declined on an average 1.74 percentage points in Bangladesh between 2000 and 2010 against the MDG target of 1.20 percentage points. The estimated poverty headcount ratio for 2013 is 26.2 percent. Bangladesh has already met one of the indicators of target 1 by bringing down the poverty gap ratio to